Pengaruh Inaportnet Terhadap Efektivitas Clearance In/Out Kapal Pada Pt Oremus Bahari Mandiri Surabaya - Markus Asta Patma Nugraha; Alwin (LOGISTIK, 2022)
Indonesia is known as the largest archipelagic country in the world and has a strategic location between the two continents of Asia and Australia. So this causes a lot of export and import of goods. Thus, Inaportnet, which is an electronic portal for fast and accurate port service information, is very important. This study aims to determine the effect of Inaportnet on the effectiveness of ship in/out clearance at PT Oremus Bahrari Mandiri Surabaya. This research is a descriptive quantitative research. The data collection was carried out at PT Oremus Bahari Mandiri Surabaya in June 2019 by means of observation, documentation studies, and distributing questionnaires. This research applies validity test, reliability test, simple linear regression method and coefficient of determination. The results show that in general, Inaportnet at PT Oremus Bahari Mandiri Surabaya has been running well, as can be seen from the readiness carried out by the Port Authority. This readiness includes facilities and human resources / operators, as well as service user support. Integrated services for ships and goods electronically have been running well. Furthermore, based on the results of the regression analysis that has been obtained, it shows that Inaportnet has a positive and significant effect with an R2 value of 0.804 or 80.4% on the effectiveness of Clearance in/out Ships at PT Oremus Bahari Mandiri Surabaya